INITIAL EXPERIENCE WITH HYBRID APPROACH FOR HYPOPLASTIC LEFT HEART SYNDROME - Imanov, E.E.; Dytkyvskyi, I.O.; Plyska, O.I.; Lazoryshynets, V.V.; Abdullayev, F.Z. (World of Medicine and Biology, 2025)
With the purpose of assess the experience of off-pump hybrid approach for palliation of hypoplastic left heart syndrome 15 neonates included in the study. The mean diameter of the ascending aorta was 2.08±0.14mm. 6 (40 %) patients had concomitant large ventricular septum defect. Hybrid palliation surgery included bilateral banding of pulmonary artery branches to 2.5–3.5 mm in 15 patients, supplemented by endovascular stent implantation in the lumen of the patent ductus arteriosus in 15 patients; balloon atrial septostomy – in 6 (40 %) patients. In-hospital mortality comprised 60 % (n=9): 6 (66.7 %) – due to heart failure; 2 (22.2 %) – due to septic pneumonia; in 1 (11.1 %) – Rashkind procedure complicated with left atrium perforation. 4 (26.7 %) patients discharged with improvement. In neonates with extremely high risk of performing Norwood I-Blalock /Sano, the alternative is off-pump hybrid palliative intervention, serving like a life-supporting “bridge” either to Norwood–Glenn surgery, and/or subsequent heart transplantation.
Keywords: hypoplastic left heart syndrome; hybrid palliation surgery; Norwood surgery; balloon atrial septostomy; neonates